Expanding Sequence

Calculus Level 4

lim n + ( 1 n 2 + 1 + 2 n 2 + 2 + 3 n 2 + 3 + . . . + 66 n 1 n 2 + 66 n 1 + 66 n n 2 + 66 n ) \lim_{n\to+\infty} \left( \frac{1}{n^2+\sqrt{1}} + \frac{2}{n^2+\sqrt{2}} + \frac{3}{n^2+\sqrt{3}} + ... + \frac{66n-1}{n^2+\sqrt{66n-1}} + \frac{66n}{n^2+\sqrt{66n}} \right)

Evaluate the limit above.

Notice that the 1st element of the sequence is the sum of 66 numbers, the 2nd one of 132 numbers, the 3rd one of 198 numbers and so on.


The answer is 2178.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Lorenzo Calogero
Nov 14, 2017

n 2 + k = n 2 + o ( n 2 ) n^2 + \sqrt{k} = n^2 + o(n^2) and n 2 + a n b = n 2 + o ( n 2 ) n^2 + \sqrt{an-b} = n^2 + o(n^2) when n + n\to+\infty k , a , b N \forall k, a, b \in \mathbb{N} . Therefore: lim n + ( 1 n 2 + 1 + 2 n 2 + 2 + 3 n 2 + 3 + . . . + 66 n 1 n 2 + 66 n 1 + 66 n n 2 + 66 n ) = \lim_{n\to+\infty} \left( \frac{1}{n^2+\sqrt{1}} + \frac{2}{n^2+\sqrt{2}} + \frac{3}{n^2+\sqrt{3}} + ... + \frac{66n-1}{n^2+\sqrt{66n-1}} + \frac{66n}{n^2+\sqrt{66n}} \right) = = lim n + ( 1 n 2 + o ( n 2 ) + 2 n 2 + o ( n 2 ) + 3 n 2 + o ( n 2 ) + . . . + 66 n 1 n 2 + o ( n 2 ) + 66 n n 2 + o ( n 2 ) ) = = \lim_{n\to+\infty} \left( \frac{1}{n^2+o(n^2)} + \frac{2}{n^2+o(n^2)} + \frac{3}{n^2+o(n^2)} + ... + \frac{66n-1}{n^2+o(n^2)} + \frac{66n}{n^2+o(n^2)} \right) = = lim n + 1 + 2 + 3 + . . . + 66 n n 2 + o ( n 2 ) = = \lim_{n\to+\infty} \frac{1+2+3+...+66n}{n^2+o(n^2)} = = lim n + 66 n ( 66 n + 1 ) 2 n 2 + o ( n 2 ) = = \lim_{n\to+\infty} \frac{\frac{66n(66n+1)}{2}}{n^2+o(n^2)} = = lim n + 6 6 2 n 2 + 66 n 2 n 2 + o ( n 2 ) = = \lim_{n\to+\infty} \frac{66^2 n^2 + 66n}{2n^2+o(n^2)} = = lim n + 6 6 2 n 2 + o ( n 2 ) 2 n 2 + o ( n 2 ) = = \lim_{n\to+\infty} \frac{66^2 n^2 + o(n^2)}{2n^2+o(n^2)} = = lim n + 6 6 2 n 2 2 n 2 = 6 6 2 2 = 2178 = \lim_{n\to+\infty} \frac{66^2 n^2}{2n^2} = \frac{66^2}{2} = \boxed{2178}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...